Changes In Investment Behavior of the Millennial Generation Before & During the Covid-19 Pandemic - Hindriati Pangestu; Maria Rio Rita (PT Mattawang Mediatama Solution, 2024)
The aim of the research is to find out whether there has been a change in the investment behavior of the millennial generation before and during the Covid-19 pandemic. This research used a quantitative research approach. This study was conducted in Salatiga City, Central Java Province. The sampling technique used purposive sampling, with total sample was 100 respondents from the millennial generation. The results of the research show that there has been a change in the investment behavior of the millennial generation before and during the Covid-19 pandemic. Before the Covid-19 pandemic, the millennial generation preferred short-term investments because of the uncertainty of the income they would receive, whereas during the Covid-19 pandemic, the millennial generation chose short-term investments because they were minimal. risk. If we look at the type of investment before the Covid-19 pandemic, the generation preferred stock investment, while during the Covid-19 pandemic they preferred mutual funds.